Visually Perceived Negative Emotion Enhances Mismatch Negativity but Fails to Compensate for Age-Related Impairments - Chen, Jiali; Huang, Xiaomin; Wang, Xianglong; Zhang, Xuefei; Liu, Sishi; Ma, Junqin; Huang, Yuanqiu; Tang, Anli; Wu, Wen (Frontiers in Human Neuroscience, 2022)
Objective: Automatic detection of auditory stimuli, represented by the mismatch negativity (MMN), facilitates rapid processing of salient stimuli in the environment. The amplitude of MMN declines with ageing. However, whether automatic detection of auditory stimuli is affected by visually perceived negative emotions with normal ageing remains unclear. We aimed to evaluate how fearful facial expressions affect the MMN amplitude under ageing. Methods: We used a modified oddball paradigm to analyze the amplitude of N100 (N1) and MMN in 22 young adults and 21 middle-aged adults. Results: We found that the amplitude of N1 elicited by standard tones was smaller under fearful facial expressions than neutral facial expressions and was more negative for young adults than middle-aged adults. The MMN amplitude under fearful facial expressions was greater than neutral facial expressions, but the amplitude in middle-aged adults was smaller than in young adults. Conclusion: Visually perceived negative emotion promotes the extraction of auditory features. Additionally, it enhances the effect of auditory change detection in middle-aged adults but fails to compensate for this decline with normal ageing. Significance: The study may help to understand how visually perceived emotion affects the early stage of auditory information processing from an event process perspective.